Chromium (VI), nickel and polycyclic aromatic hydrocarbons and lung cancer - Silva, Maria João (2021)
Problem formulation: In workplace environments the most common exposure scenario implies workers coexposure to multiple chemicals during tasks performance; Occupational exposure limits (OEL) – prevention of morbidity and mortality from exposure to individual chemical stressors in the workplace but do not account for all the complexities of the workplace environment. There is a need for occupational risk assessment tools that integrate the combined risk from exposure to multiple chemicals, and the possibility that such exposures may cause interactions or modify the toxic effects - cumulative risk.